The Mission and Role of the Social Educator in the Development of the Educational Environment of the Educational Institution - Чуйко, Олена Василівна (Київський національний університет імені Тараса Шевченка, 2019)
The last three years have been associated with a change in the status of social pedagogy as a branch of scientific knowledge and professional practice, as a result of which it was transferred from the pedagogical branch to the branch of social work. In addition, serious social changes in Ukraine, related both to the development of democracy in society, the implementation of humanitarian reforms, and the emergence of a number of social problems (war, population migration, poverty, the crisis of the family institution, etc.), indicate the need for changes in the field of professional assistance aimed at ensuring the psychological well-being of citizens. Today, there is some uncertainty regarding the main aspects of the profession of a social educator in society. But the content of this activity in the context of the deployment of professional practices in educational institutions, in particular in a secondary school, causes no less contradictions. The main idea is to autonomize the position of a social educator. A social educator should become a conductor of the philosophy and policy of the functioning of the educational environment, which is safe for the child, humanistically oriented, developing personal potential, providing appropriate material, physical, psychological, spiritual resources. His activities should be aimed at a critical assessment of the team's progress towards progress, a clear response to the negative social influences of the educational environment on the personality of the child, participation in planning the impact of events on the personality of the child and the acquisition of a positive socialization experience. His mission is to improve the quality of human life through the harmonization of human-environment relations, and the goal of the activity is to create conditions for positive socialization and effective integration of man in society.

На сьогодні існує певна невизначеність щодо засадничих аспектів професії соціального педагога в суспільстві. Не менше протиріч викликає зміст цієї діяльності в контексті розгортання професійних практик у закладах освіти, зок- рема в загальноосвітній школі. Головна ідея полягає в автономізації позиції соціального педагога, який формулює місію і цілі освітнього закладу, упроваджує філософію і політику "піклувальної практики" впливу освітнього середо- вища на психіку учня в досягненні ним психологічного благополуччя.
Місія і роль соціального педагога в розбудові освітнього середовища закладу освіти
Keywords: соціальна педагогіка; місія; роль і функції соціального педагога; психологічна служба закладу освіти; психічне здоров'я; психологічне благополуччя; Діамантова модель; суб'єктні стосунки.; social pedagogy; mission; role and functions of a social educator; psychological service of an educational institution; mental health; psychological well-being; Diamond Model; subjective relations.